Theoretical Review of Restorative Justice as a Breakthrough in Resolving Legal Cases by the Indonesian National Police - Pinem, Serimin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to analyze restorative justice as a breakthrough in resolving legal cases by the Police of the Republic of Indonesia from a theoretical perspective. Data was collected through literature study, observation, and analysis of legislation and other relevant documents. Data analysis uses the interactive model from Miles and Huberman. The research results show that, in the Indonesian context, there are several positive impacts that can be identified related to the application of restorative justice in resolving legal cases as follows: 1) Relationship Restoration, helping to restore the relationship between the perpetrator and the victim; 2) Reducing recidivism, restorative justice can reduce the rate of perpetrators returning to the world of crime; 3) Legal System Efficiency, speeding up the case resolution process, reducing the burden on an already congested legal system, and saving resources, including time and money; 4) Community Participation, involving the community in the case resolution process; 5) Psychological Support, providing psychological support for victims; 6) Alternatives for Young Offenders, a more useful alternative to prison for young offenders. However, the future challenge for the police is not to let restorative justice become a commercial product of the police